A quantitative method to measure and evaluate the peelability of shrimps (Pandalus borealis). (August 2018) - Gringer, Nina; Dang, Tem Thi; Orlien, Vibeke; Olsen, Karsten; Bøknæs, Niels; Jessen, Flemming
Abstract: A novel, standardized method has been developed in order to provide a quantitative description of shrimp peelability. The peeling process was based on the measure of the strength of the shell-muscle attachment of the shrimp using a texture analyzer, and calculated into the peeling work. The self-consistent method, insensitive of the shrimp size, was proven valid for assessment of ice maturation of shrimps. The quantitative peeling efficiency (peeling work) and performance (degree of shell removal) showed that the decrease in peeling work correlated with the amount of satisfactory peeled shrimps, indicating an effective weakening of the shell-muscle attachment. The developed method provides the industry with a quantitative analysis for measurement of peeling efficiency and peeling performance of shrimps. It may be used for comparing different maturation conditions in relation to optimization of shrimps peeling. Highlights: A novel method for quantitative measurement of shrimp peelability. The strength of the shell-muscle attachment is described using a texture analyzer. This method can be used by the industry for optimizing shrimp processing.